Coke-oven wastewater treatment in a dual-chamber microbial fuel cell with thiocyanate-degrading biofilm enriched at the air cathode. (10th March 2022) - Yamada, Kaho; Fukushima, Toshikazu; Freguia, Stefano
Abstract: Coke-oven wastewater is usually treated with the activated sludge process, which requires large amounts of electrical energy for aeration and sludge disposal. A more sustainable treatment is strongly required. Recently, microbial fuel cells (MFCs) are focused as a technology for the production of electricity from wastewaters with simultaneous removal of organic matter. However, no MFC has been reported that can remove phenol, thiosulfate and thiocyanate simultaneously without aeration. Phenol can generally be removed well, whereas thiocyanate is relatively difficult to degrade. In this study, a dual-chamber MFC (D-MFC) was designed and equipped with a thiocyanate-degrading biofilm enriched on an air cathode. The D-MFC degraded phenol and thiosulfate in the anode chamber at the rate of 104 and 331 mg/L/day, respectively and subsequently degraded thiocyanate in the cathode chamber at the rate of 250 mg/L/day. The D-MFC showed high thiocyanate degradation rate. This suggests that pre-enrichment could accelerate thiocyanate degradation in MFC. In addition, thiocyanate degradation was not inhibited by phenol as thiocyanate was removed in the cathode chamber after phenol was removed in the anode chamber. This study demonstrated the feasibility of treating coke-oven wastewater by a D-MFC with a thiocyanate-degrading biofilm enriched at the air cathode. HIGHLIGHTS: A dual-chamber microbial fuel cell achieved simultaneous phenol, thiosulfate and thiocyanate degradation without active aeration. Pre-enrichment on an air cathode could accelerate thiocyanate degradation in MFC. The membrane is essential to avoid inhibition of thiocyanate degradation by phenol. Graphical Abstract